Piezoresistive Sensor Based on Micrographite-Glass Thick Films - Osvaldo Correa; Pompeu Pereira de Abreu Filho; Stanislav Moshkalev; Jacobus Swart (Sensors, 2022)
A new Pb-free glass containing several oxides (Bi2O3, B2O3, SiO2, Al2O3 and ZnO) with sintering temperature reduced down to 600 °C has been developed for applications in a piezoresistive pressure sensor. Using this low sintering temperature glass, it was possible to fabricate micrographite-based pastes and piezoresistive films without losses of graphitic material during the sintering. Good adherence of the films onto alumina substrates was observed and attributed in part to the reactions of ZnO and Bi2O3 with alumina substrates. Piezoresistive films with uniformly distributed micrographite particles were produced using sodium carboxymethyl cellulose (NaCMC) in aqueous solutions during the preparation of pastes. NaCMC plays a decisive role in interactions between micrographite particles and glassy matrix, providing good wettability of glass powder particles and homogeneous distribution of MG particles in the pastes. Finally, excellent repeatability of the sensor response to the applied deformations was verified in cycling experiments when the sample was submitted to 1000 load/release cycles. These results demonstrated very high stability of the sensor response (within ±1%), and also evidenced high stability of the film under the cyclic strain loads and good film adherence to the substrate.